MEMAJUKAN KEBUDAYAAN NASIONAL INDONESIA - Amri Marzali (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
In this article a definition of culture is proposed in relation with the program of “the development of the Indonesian Culture.” This program, which is stated in the Indonesian Constitution, article No. 32, is the responsibility of the government of the Republic Indonesia to implement. The proposed definition is a result of an explorative study on the definitions of culture used in four important sources. The sources are anthropology, various disciplines of science beyond anthropology, articles written by Indonesian cultural thinkers and a document published by UNESCO in 1983. Culture, according to the proposed definition is “the capacity or capabilities of the intellectual, emotional, and spiritual features of a social group which function to enhance the human dignity of the group.” By using this definition, it is hoped, the government of the Republic Indonesia will be able to design a public policy on “the development of the Indonesian Culture”, which is both modifiable and measurable.